Statement from the 71st Greater Horn of Africa Climate Outlook Forum (GHACOF 71) - IGAD Climate Prediction and Applications Centre (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
The 71st Greater Horn of Africa Climate Outlook Forum (GHACOF71) was held in Nairobi from August 25-26, 2025. The forum was organised by the IGAD Climate Prediction and Applications Centre (ICPAC) in collaboration with the National Meteorological and Hydrological Services (NMHSs) across the Greater Horn of Africa, the World Meteorological Organisation (WMO), and international partners. The forum reviewed and documented the progress and impacts of the June to September (JJAS) 2025 season, released the consolidated objective regional climate outlook for the October-December (OND) 2025 season, discussed the implications of the OND 2025 climate forecast, and developed practical advice for managing climate risks in various climate-sensitive sectors. The GHA region comprises Burundi, Djibouti, Eritrea, Ethiopia, Kenya, Rwanda, Somalia, South Sudan, Sudan, Tanzania, and Uganda. The forum included representatives from disaster risk management, agriculture, livestock, water resources, health, and conflict prevention sectors, along with media, NGOs, humanitarian organisations, and development partners who engaged in co-producing mitigation strategies, ensuring that the outlook and advisories are relevant, actionable, and supportive of resilience building across the region.